Measurement of W± Z production cross sections and gauge boson polarisation in pp collisions at √s = 13 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2019)
This paper presents measurements of W± Z production cross sections in pp collisions at a centre-of-mass energy of 13 TeV. The data were collected in 2015 and 2016 by the ATLAS experiment at the Large Hadron Collider, and correspond to an integrated luminosity of 36.1 fb−1. The W± Z candidate events are reconstructed using leptonic decay modes of the gauge bosons into electrons and muons. The measured inclusive cross section in the detector fiducial region for a single leptonic decay mode is σ fid. W± Z→ l' v ll = 63.7 ± 1.0 (stat.) ± 2.3 (syst.) ± 1.4 (lumi.) fb, reproduced by the next-to-next-to-leading-order Standard Model prediction of 61.5+1.4 −1.3 fb. Cross sections for W+ Z and W− Z production and their ratio are presented as well as differential cross sections for several kinematic observables. An analysis of angular distributions of leptons from decays of W and Z bosons is performed for the first time in pair-produced events in hadronic collisions, and integrated helicity fractions in the detector fiducial region are measured for the W and Z bosons separately. Of particular interest, the longitudinal helicity fraction of pair-produced vector bosons is also measured.